IPF Respiratory Symptoms Management — Current Evidence - Janowiak, Piotr; Szymanowska-Narloch, Amelia; Siemińska, Alicja (Frontiers in Medicine, 2022)
Idiopathic pulmonary fibrosis (IPF) is a progressive, chronic disease of the lungs which is characterized by heavy symptom burden, especially in the last year of life. Despite recently established anti-fibrotic treatment IPF prognosis is one of the worst among interstitial lung diseases. In this review available evidence regarding pharmacological and non-pharmacological management of the main IPF symptoms, dyspnea and cough, is presented.